(untitled) (INNOVATIVE ECONOMY, 2026)
Lobodina Z.M., Trush V.L. ASSIMILATION OF FINANCIAL INSTRUMENTS FOR INCLUSIVE DEVELOPMENT OF COMMUNITIES IN THE NORDIC COUNTRIES INTO THE EXPERIENCE OF UKRAINE Purpose. The aim of the article is to systematize the experience of Northern European countries in using financial instruments to ensure inclusive community development and to substantiate a conceptual model for adapting these instruments to Ukrainian practice, taking into account existing institutional capacity and constraints. Methodology of research. A set of general scientific and special methods was used in the process of research, in particular: methods of theoretical generalization and systematization – to reveal the essence of inclusive development and its financial support; comparative analysis – to compare the indicators of inclusive growth of Ukraine and the Nordic countries; statistical methods – for assessing the Inclusive Growth Index (IGI) and its components; institutional approach – to study the peculiarities of the functioning of financial mechanisms at the community level; logical modelling – to form proposals for adapting the Nordic experience. Findings. It has been established that the financial architecture of inclusive development in the Nordic countries is based on a combination of three main instruments: aggregate municipal borrowing through specialized financial institutions, a developed market of green bonds of local self-government and a model of social investments in the formation of budget priorities. It is proved that the effectiveness of this system is ensured by a high level of fiscal autonomy, institutional trust and transparency of management. The analysis of the Inclusive Growth Index showed that Ukraine is significantly lagging behind the Nordic countries, which is due to structural imbalances in the economic, social and environmental spheres. At the same time, it is determined that the decentralization reform has created the basic prerequisites for the introduction of modern financial instruments for community development. Originality. The theoretical and practical foundations for developing a financial mechanism for inclusive community development through the integration of the Nordic model into the Ukrainian context have been further explored. A conceptual approach to the phased assimilation of financial instruments is proposed, which takes into account institutional limitations and specifics of the national economy, and the role of social capital as a determining factor in the effectiveness of financial innovations at the local level is substantiated. Practical value. The obtained results can be used by state and local government authorities in formulating policies for the development of local communities. The proposed approaches can be applied to create a local self-government financing agency, develop the municipal green bond market, as well as improve the mechanisms for financing social services on the basis of performance. The results of the study can serve as an analytical basis for developing strategies for post-war recovery and ensuring inclusive economic growth. Key words: inclusive development, territorial communities, financial instruments, decentralization, municipal financing, green bonds, social investments, inclusive growth index.